Monitoring the agri-food system in Myanmar: Food vendors - May 2021 survey round - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
This Research presents the results from seven rounds of a telephone survey with food vendors conducted in rural and urban zones throughout Myanmar, focusing more specifically on the results from the last round completed in May 2021. The purpose of the survey is to provide data and insights to interested stakeholders in order that they better understand the effects of shocks related to COVID-19 and the ongoing political crisis on Myanmar’s food markets. In particular, the explores COVID-19 prevention measures, changes in shopping behavior, difficulties in food vendor operations due to the COVID-19 and political crises, changes in availability and prices of foods, and perceived changes in consumption.